PERAN ANGGARAN SEBAGAI ALAT PENGAWASAN BIAYA OPERASIONAL PT PELAYARAN NASIONAL SAMUDERA RAYA JAKARTA - Darmeinis; Aris Widayanto (Lembaga Pengembangan Kinerja Dosen, 2022)
PT Pelayaran Samudra Raya continues to strive to improve efficiency in its operational activities to provide the best quality service for customers. To achieve this efficiency, the use of costs must be done optimally so as to produce good performance for the company. To oversee the use of the company's operational costs, management needs a budget that can provide an overview of the optimal costs in the company's operational activities. Budgets that are prepared and monitored properly can help achieve efficiency in the use of company operational costs. Results of the analysis of variance carried out on PT Samudera Raya's operational costs during 2019 to 2021 showed improvements in the preparation of the budget and the use of the company's operational costs. This can be seen from the percentage of variance that decreases every year, which is 2.11% in 2019, 1.13% in 2020 and a variance of 0.28% in 2021. The use of the company's operational costs has been monitored properly by the accounting department. and supervisors of the company's fleet both before the Covid19 pandemic occurred and while it was taking place. All cash disbursements that occur in each ship's trip must be accounted for by the captain once the trip is completed, cost deviations that occur outside the plan must be explained in detail by the cause and effect by the fleet, the difference between the realization of costs and the budget must be considered in the preparation of the budget for the next ship trip. The preparation of the company's operational cost budget has been carried out for the last 3 years and continues to be evaluated every year to take corrective actions to reduce the occurrence of variances, especially those that are not profitable for the company. The use of the budget as a means of monitoring the company's operational costs is able to achieve the expected results. Although it is not maximized because there is still a difference between the budget and the realization of costs, the difference can be reduced every year. The difference between the budget and the realization of the company's operational costs has decreased in the last 3 years. This shows an improvement from the company's management in optimizing the budget function as a means of controlling the company's operational costs.